A temperature of 20°C in the UK winter: a sign of the future?. (4th August 2020) - Kendon, Mike; Sexton, David; McCarthy, Mark
Abstract : In February 2019, 21.2°C was recorded at Kew Gardens, exceeding the previous UK winter record by a margin of 1.5°C. Observational data show that this event resulted from exceptional synoptic conditions, however, human‐induced climate change may have increased the margin by which the record was broken. Model simulations of the UK's future climate show that if emissions remain high, it is likely that every other winter in the late twenty‐first century will experience at least 1–2 days that beat the historical record.